Anomalous Type 17 Response to Viral Infection by CD8(+) T Cells Lacking T-bet and Eomesodermin - Intlekofer, Andrew M. (2008)
When intracellular pathogens invade mammalian hosts, naïve CD8(+) T cells differentiate into cytotoxic killers, which lyse infected target cells and secrete cytokines that activate intracellular microbicides. We now show that CD8(+) T cells deficient in the transcription factors T-bet and eomesodermin (Eomes) fail to differentiate into functional killers required for defense against lymphocytic choriomeningitis virus. Instead, virus-specific CD8(+) T cells lacking both T-bet and Eomes differentiate into an IL-17-secreting lineage, reminiscent of the helper T cell fate that has been implicated in autoimmunity and extracellular microbial defense. Upon viral infection, mice with T cells lacking both T-bet and Eomes develop a CD8(+) T cell-dependent, progressive inflammatory and wasting syndrome characterized by multi-organ infiltration of neutrophils. T-bet and Eomes, thus, ensure that CD8(+) T cells adopt an appropriate course of promoting intracellular rather than extracellular destruction.